Islamic Social Entrepreneurship and Work Ethics in Global Business - Siompu, Irfan; Asfiah, Nurul (Formosa Journal of Applied Sciences, 2024)
Social entrepreneurship refers to business efforts that focus not only on profits but also on creating social value. In the Islamic context, social entrepreneurship is based on sharia principles which emphasize community welfare and social justice. This research uses a qualitative approach. Talking about Islamic social entrepreneurship, this concept does not only emphasize the financial aspect, but also the social impact produced by a business. . It is impossible to separate the implementation of entrepreneurial operations from the impact it will have on surrounding environmental conditions. demonstrate the integration of ethics in entrepreneurship education and broader societal awareness. but also on the social impact produced by a business. such as blessings in business, sharing good fortune with others, and fairness in business are strong foundations for Muslim entrepreneurs in running their businesses.